2016
DOI: 10.1007/s12264-016-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Ethanol Preconditioning Protects Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Neuronal Injury By Activating Large Conductance, Ca2+-Activated K+ Channels In Vitro

Abstract: Increasing evidence suggests that low to moderate ethanol ingestion protects against the deleterious effects of subsequent ischemia/reperfusion; however, the underlying mechanism has not been elucidated. In the present study, we showed that expression of the neuronal large-conductance, Ca 2? -activated K ? channel (BK Ca ) asubunit was upregulated in cultured neurons exposed to oxygen-glucose deprivation/reoxygenation (OGD/R) compared with controls. Preconditioning with low-dose ethanol (10 mmol/L) increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…As melatonin is sparingly soluble, solubility enhancers, such as ethanol, are used. Ethanol could confound previous studies of melatonin protection 13,[15][16][17][18][19] , as low-dose ethanol ~4 h after HI is protective in adult models of stroke [20][21][22] . In a previous piglet study, we observed augmentation of HT protection with 30 mg/kg/24 h melatonin with ethanol excipient when started 10 mins after hypoxia-ischemia (HI), reaching blood levels >15 mg/l within 1 h 13 .…”
mentioning
confidence: 99%
“…As melatonin is sparingly soluble, solubility enhancers, such as ethanol, are used. Ethanol could confound previous studies of melatonin protection 13,[15][16][17][18][19] , as low-dose ethanol ~4 h after HI is protective in adult models of stroke [20][21][22] . In a previous piglet study, we observed augmentation of HT protection with 30 mg/kg/24 h melatonin with ethanol excipient when started 10 mins after hypoxia-ischemia (HI), reaching blood levels >15 mg/l within 1 h 13 .…”
mentioning
confidence: 99%
“…Many researches (Chi et al, 2010;Gribkoff et al, 2001;Hewawasam et al, 2003;Li et al, 2014;Su et al, 2017) have shown that BK Ca channel is one of the molecular targets of the ischemic stroke. Therefore, we tested whether vitamin C could activate the BK Ca channel.…”
Section: Vitamin C Activates Bk Ca Channelsmentioning
confidence: 99%
“…Activation of BK Ca channel can cause hyperpolarization of membrane potential, which participates in regulation of neurons functions . The pharmacological application has demonstrated a protective role of BK Ca channel against ischaemic injury, such as that low dose ethanol preconditioning protects primary rat cortical neurons from anoxia/reoxygenation (A/R)‐induced injury by activating BK Ca channel . Although TFR could activate the K Ca channel in cerebral artery VSMCs, whether it has a direct effect on nerve cell to produce neuroprotection, especially its action on neuronal K Ca channel, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The pharmacological application has demonstrated a protective role of BK Ca channel against ischaemic injury, such as that low dose ethanol preconditioning protects primary rat cortical neurons from anoxia/ reoxygenation (A/R)-induced injury by activating BK Ca channel. [16] Although TFR could activate the K Ca channel in cerebral artery VSMCs, whether it has a direct effect on nerve cell to produce neuroprotection, especially its action on neuronal K Ca channel, is unclear. The present study was therefore designed to investigate the effect of TFR against H/R injury in rat hippocampal neurons and its mechanism related to BK Ca channel.…”
Section: Introductionmentioning
confidence: 99%